The Influence of Influencers and Product Quality on Shopee Buying Interest Mediated by Consumer Trust - Muhammad Sholahudin; Alvin Rio Sanjaya; Alif Radhia Rahman (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study reveals seven key findings related to factors that influence consumer purchase intention on e-commerce platforms such as Shopee. Influencers have a significant influence on purchase intention, while product quality does not have a direct impact, but plays a role in building consumer trust. Consumer trust is proven to have a strong influence on purchase intention. Brand quality relationships and brand image mediate the influence of social media on purchase intention on Shopee. In addition, product quality contributes to increasing consumer trust, which then influences purchase intention. The results of the study confirm that consumer trust is a crucial element in determining purchase intention, with product quality as the main foundation in building this trust. To increase purchase intention on Shopee, sellers are advised to improve product quality, provide transparent product descriptions, and provide responsive customer service. Marketing strategies through influencers and social media can strengthen brand relationships and product image. Sellers also need to utilize e-commerce features such as product reviews and promotions to build consumer trust and attract purchase intention. These findings provide strategic guidance for sellers in optimizing sales performance on e-commerce platforms.